Mobile Virtual Work
DOI: 10.1007/3-540-28365-x_5
|View full text |Cite
|
Sign up to set email alerts
|

Virtually Connected, Practically Mobile

Abstract: This chapter addresses a central issue in studies of mobile work and mobile technology -what is the work of mobile workers, and how do they use the resources that they have to undertake this work (i.e. the work they have to do in order to do their work)? In contrast to many of the other papers in this collection, the objective of this chapter is to examine individual mobile work, and not teamwork and co-operation other than where it impacts on the work of individuals. We present data from a study of mobile wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Similarly, Matthews and colleagues [10] found that context, namely other devices, tasks, and places, also constrained people's use of their smart phones. Consistent with earlier work [16,17,18], they observed that people often used their phones to "fill time" in the absence of counter-pressures such as pending activities or the presence of others. These findings provide insight into current smart phone practices but also raise the additional questions of whether smart phones are inherently only suitable for certain tasks or whether selective usage patterns evolved from prior behavior and perceptions.…”
Section: Related Worksupporting
confidence: 85%
“…Similarly, Matthews and colleagues [10] found that context, namely other devices, tasks, and places, also constrained people's use of their smart phones. Consistent with earlier work [16,17,18], they observed that people often used their phones to "fill time" in the absence of counter-pressures such as pending activities or the presence of others. These findings provide insight into current smart phone practices but also raise the additional questions of whether smart phones are inherently only suitable for certain tasks or whether selective usage patterns evolved from prior behavior and perceptions.…”
Section: Related Worksupporting
confidence: 85%
“…With regard to establishing workplaces across several locations, Perry and Brodie (2006) highlight the importance of taking into consideration the development of tools to allow people to set up their temporary workplaces. In fact, a lot of effort is put into organising and packing things that will be necessary to conduct work at a new location, since such work usually is dependent on information, technological or even Space and place are often treated as different elements.…”
Section: Place-centred Frame: Nomadicity As Situated Work In Multiplementioning
confidence: 99%
“…Also, considerable effort is invested in discovering the resources needed to lay the supportive apparatus down and to make it work (Mark and Su 2010). All these activities developed prior to the formal work is called mobilisation work by Perry and Brodie (2006), i.e. the work done to get nomadicity started.…”
Section: Place-centred Frame: Nomadicity As Situated Work In Multiplementioning
confidence: 99%
See 1 more Smart Citation
“…However, work for these workers does not follow the traditional image of home-working on the kitchen table or in the spare room. Rather the model is that of the nomadic worker, much of whose work-week may involve being on-site at various contractors or employers (Perry and Brodie, 2005).…”
Section: The Built Environmentmentioning
confidence: 99%